2021
DOI: 10.1016/j.jadohealth.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis of Demographic and Behavioral Risk Factors of Severe Acute Respiratory Syndrome Coronavirus 2 Seropositivity Among a Sample of U.S. College Students

Abstract: Purpose Colleges and universities across the United States are developing and implementing data-driven prevention and containment measures against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Identifying risk factors for SARS-CoV-2 seropositivity could help to direct these efforts. This study aimed to estimate the associations between demographic factors and social behaviors and SARS-CoV-2 seropositivity and self-reported positive SARS-CoV-2 diagnostic test. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…The parent study was a randomized controlled trial evaluating the effect of receiving SARS‐CoV‐2 antibody test results on participants’ compliance with protective behavior against COVID‐19 [ 33 ]. Details regarding the parent study and overall study design are published elsewhere [ 14 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent study was a randomized controlled trial evaluating the effect of receiving SARS‐CoV‐2 antibody test results on participants’ compliance with protective behavior against COVID‐19 [ 33 ]. Details regarding the parent study and overall study design are published elsewhere [ 14 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol consumption causes cognitive distortion and brings about behavioral changes that could increase the risk of SARS‐CoV‐2 transmission and infection [ 12 , 13 , 14 ]. It weakens vigilance, information processing, spatial working memory and performance of complex tasks and increases impulsivity [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, this study has shown that BD is prevalent in Japan, that fewer people engaged in BD during the COVID-19 pandemic and that BD is associated with reduced odds for engaging in several COVID-19 preventive behaviors. Given that alcohol use has also been linked to other negative coronavirus-related outcomes ( Kianersi et al, 2021 , Lassen et al, 2021 , Saurabh et al, 2021 ), the results of this study highlight the importance of public health messaging about the potential consequences of heavy alcohol use during the current pandemic ( Nordeck et al, 2022 ). In addition, they also indicate that implementing measures to detect harmful drinking such as alcohol screening in health care settings ( Sugarman and Greenfield, 2021 ) may also be potentially efficicious.…”
Section: Discussionmentioning
confidence: 82%
“…This may have important public health implications not only because the prevalence of BD was already high in Japan before the coronavirus pandemic began ( Bergmark and Kuendig, 2008 , World Health Organisation, 2018 ) but also because recent research from other countries has shown that increased alcohol consumption ( Ebrahimi et al, 2021 ), BD ( Einberger et al, 2021 , Suffoletto et al, 2020 ) and alcohol abuse ( Taylor et al, 2021 ) are all linked to non-compliance with COVID-19 preventive measures. Together with other research that has linked alcohol consumption to symptomatic (vs. asymptomatic) COVID-19 infection ( Saurabh et al, 2021 ), SARS-CoV-2 seropositivity and a self-reported infection history ( Kianersi et al, 2021 ) and an increased risk for developing acute respiratory distress syndrome (ARDS) when hospitalized for COVID-19 ( Lassen et al, 2021 ), this highlights the importance of research focused on alcohol use and misuse during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 75%
“…Until late in 2020, no vaccine was readily available in the United States and eligibility for typical college-aged students was limited until Spring 2021. In addition, in some places, college students engaged in behaviors that increased the risk of infection such as gathering in Greek organization activities, having multiple sexual partners, and frequent alcohol consumption ( Kianersi et al, 2021 ). Hoyt et al (2021) reported that college students reported a sharp increase in anxiety around health issues during the pandemic.…”
Section: Introductionmentioning
confidence: 99%